65.7k views
3 votes
(3a3 − 5b3) + a3 + b3 = (a3 + b3).

1 Answer

4 votes
STEP 1: Cancel equal terms on both sides of the equation
(3a × 3 - 5b × 3) + a × 3 + b × 3 = a × 3 + b × 3
(3a × 3 - 5b × 3) + b × 3 = 0 + b × 3
-5b × 3 + 3a × 3 = 0
-15b + 9a = 0

STEP 2: When there is a "+" in front of the parenthesis the expression remains the same
-15b + 9a = 0
9a - 15b = 0

STEP 3: Move variable to the right side and change its sign
9a - 15b = 0
9a = 15b

STEP 4: Divide both sides by 9
a = 5/3b
User Rndm
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.